Sinusitis among Patients Undergoing CT Scan of Paranasal Sinuses in a Tertiary Care Centre: A Descriptive Cross-sectional Study - Abhushan Siddhi Tuladhar; Anish Bhattarai; Sneha Bimali; Bibek Pokharel; Sunil Pradhan; Amit Shrestha; Riwaz Acharya (Journal of Nepal Medical Association, 2022)
Introduction: Computed tomography imaging provides detailed information about the paranasal sinuses and is now well established as an alternative to standard radiographs in evaluating patients with sinusitis. Sinusitis can have dangerous complications which can even lead to death if not diagnosed and treated on time. This study aimed to find the prevalence of sinusitis among the patients undergoing Computed Tomography scan of paranasal sinuses in a tertiary care centre.